2011
DOI: 10.1111/j.1346-8138.2011.01251.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining diabetic dermopathy

Abstract: Diabetic dermopathy presents as well-demarcated, hyperpigmented, atrophic depressions, macules or papules located on the anterior surface of the lower legs of diabetic patients. The histopathology remains poorly defined which may in part be due to the fact that the lesions are rarely biopsied. An advantage of studying autopsy material is the ease of obtaining large biopsy specimens. To further define the histopathological features of this entity, we studied tissue taken from characteristic lesions at autopsy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…In other studies, diabetic dermopathy has been reported most prevalent in 45- to 70-year-old patients and significantly associated with age (11,14,15,25), as well. Further, the mean duration of diabetes was 9.16±5.42 years and the number of dermopathy lesions was significantly associated with the duration of illness, which is in agreement with other studies (17,21,26).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…In other studies, diabetic dermopathy has been reported most prevalent in 45- to 70-year-old patients and significantly associated with age (11,14,15,25), as well. Further, the mean duration of diabetes was 9.16±5.42 years and the number of dermopathy lesions was significantly associated with the duration of illness, which is in agreement with other studies (17,21,26).…”
Section: Discussionmentioning
confidence: 70%
“…According to the available references, the prevalence of diabetic dermopathy is higher in elderly men (28), and some other studies have demonstrated that diabetic dermopathy is more prevalent in men with a significant association between gender and diabetic dermopathy (11,22,24). These findings are consistent with our investigation, which could be explained by lower number of the men than women referring to our clinic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetic dermopathy is characterized by small scar-like atrophic depressions occurring on the shins of diabetic patients; its presence is associated with microangiopathic complications of diabetes, such as nephropathy, neuropathy, and retinopathy [11]. Correlation with nephropathy and other microangiopathic complications is also seen with rubeosis facei diabeticorum.…”
Section: Diabetes Mellitusmentioning
confidence: 99%